Coconut Oil Processing Business Competitiveness Analysis In The District Of Wowonii Barat Konawe Regency Islands - Misbayana Misbayana; La Rianda; Munirwan Zani (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
AThe purpose of this study was to analyze the competitiveness of the coconut processing business and the factors that determine the competitiveness of the coconut oil processing business in the Wawonii sub-district, Konawe archipelago district. This research uses descriptive and qualitative data analysis methods with research variables, namely: (1) the profile of the coconut oil business, including the capital, labor, duration of business, raw materials, income, facilities, and infrastructure; (2) the state of the coconut oil business which includes: processing, production, and marketing technology; and (3) internal and external factors which are external factors originating from outside the person or company which include opportunities and threats, while internal factors are those originating from within the person or company which include weaknesses and strengths. Data collection techniques in this study are by means of interviews, questionnaires, and documentation, and this research's primary and secondary data sources. The stages of this research are the number of raw materials, capital, income, revenue, ratio, and productivity of the coconut oil processing business. The results of this test produce an average income of Rp. 2,796. 223 with an average capital of Rp. 3,746,278 and average business productivity of Rp. 1.90 per bottle and an average ratio of 1.7. with the results obtained from the coconut oil processing business in the West Wawonii District, Konawe Islands Regency.